Financial Inclusion and Women’s Empowerment in Pakistan - Ejaz, Mehak; Qayum, Maleeha (Pakistan Journal of Humanities and Social Sciences, 2023)
Access to financial services is crucial for economic development and poverty reduction. Unfortunately, women in Pakistan face significant barriers to accessing financial services, including formal accounts, businesses ownership, and entrepreneurship. This study aims to investigate the role of financial inclusion in empowering women and to identify the challenges they face in accessing financial services. The study is quantitative and analyses data collected from the Financial Inclusion Insights (FII) survey of 2017, with a sample size of 6,000. The study uses descriptive statistics and Chi-Square, Phi, and Cramer’s V correlation to analyse the cross-sectional data. The study found significant gender disparities in financial inclusion levels and identified the lack of financial literacy, awareness, and education and employment gaps as major hindrances for women’s access to financial services, even digital ones. The study concludes that financial inclusion and women’s empowerment have a bidirectional relationship, and recommends strengthening education, technological capabilities, and phone access, particularly for women to enhance their access and use of financial services in Pakistan.